PENGARUH POTONGAN HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN: Studi Kasus Pengguna Shopee di Kalangan Mahasiswa Fakultas Ekonomi Universitas Singaperbangsa Karawang - Mutiara Juliana; Nicodias Palasara (Jurnal Ilmiah METHONOMI, 2021)
Online shopping is currently an exchange interaction that is assisted through intermediary media, especially the purpose of buying and selling in online media. Mechanical improvements have made shopping much more profitable. During a pandemic like this, online shopping is an option for most people, especially students who want to shop at lower prices and with quality. There are two factors that influence students to make purchases, the first is a discount, and the second is the quality of a product. From the results of data processing from various tests using SPSS version 26 software, it can be found that as much as 16.8% which can affect students of the economics faculty of Singaperbangsa Karawang University in making purchases, the remaining 83.2% is influenced by other factors.